Pengembangan Perangkat Lunak Aplikasi Monitoring Klimatologi Menggunakan Metode RESTful Web service Berbasis Android (Studi Kasus : Stasiun Klimatologi Karangploso Malang) - Faisal Roufa Rohman; Arief Andy Soebroto; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Climate Monitoring is done by using sophisticated instruments that have a function to record the changing climate data. Karangploso Malang climate station is one of the station that records climate data. Variables that have been monitored such as rainfall, temperature, wind speed, and humidity. The data then sent to the Server then get processed and displayed to desktop based application and web. Desktop based application right now can't be accessed from outside the office. Web based application or mobile application can be use as alternatives so BMKG data can be accessed outside. The application that was choosed is mobile based application because it can access the climate data more faster. The mobile application get the climate data by requesting the data from a web service that use RESTful method. The data then representated in table and chart on client side. Based on design result in this research, obtained 3 functional requirements and 3 non functional requirements. Based on testing result, it is concluded that the development of software application for climate monitoring using RESTful web service method in android is meet the requirement of the design.